2008
DOI: 10.1016/s0929-6646(08)60127-8
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Glutaric Aciduria Type I by Newborn Screening in Taiwan

Abstract: With properly established cut-offs, GA1 can be successfully screened for in populations with a low incidence of the disease. Early treatment is likely to improve the outcome of cases discovered by screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
6
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 19 publications
3
6
0
1
Order By: Relevance
“…The other patient, who only had lateral limbs dyskinesia without encephalopathic crisis, showed remarkable MRI changes. Hsieh et al [12] also reported subtle basal ganglia lesions in a patient who did not experience any frank encephalopathic crisis. Long-term outcomes of these asymptomatic patients with obvious brain MRI changes are still under evaluation, and close monitoring of these patients is required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other patient, who only had lateral limbs dyskinesia without encephalopathic crisis, showed remarkable MRI changes. Hsieh et al [12] also reported subtle basal ganglia lesions in a patient who did not experience any frank encephalopathic crisis. Long-term outcomes of these asymptomatic patients with obvious brain MRI changes are still under evaluation, and close monitoring of these patients is required.…”
Section: Discussionmentioning
confidence: 99%
“…As reported by Kölker et al, [2] the frequency of acute encephalopathic crises is lower in pre-symptomatically diagnosed patients treated with Lys-restriction than with restricted protein diet; therefore, we recommended Lys-restricted combined with protein restriction for all the patients. Emergent treatment is considered essential to prevent encephalopathic crises during intercurrent illness [8,12,13]. Intercurrent illness management is the focus of GA I treatment [4], which may be accompanied with hypoglycemia, hypokalemia, ketosis, acidosis, and hyperammonemia, as well as other neurological complications.…”
Section: Discussionmentioning
confidence: 99%
“…Mutation of IVS10-2A>C (c.1244-2A>C) in children was reported in Taiwan, and also one IVS10-2A>C carrier was detected among 120 normal persons. In our study, four parents were carriers of c.1244-2A>C mutation, which would probably be hot mutation site in Chinese [13][14][15] . The c.1244-2A>C mutation causes splicing error in 10th intron and 11th exon, resulting in deletion of 5 ' terminal of 11th exon, which make GCDH enzyme activity disappeared.…”
Section: Discussionmentioning
confidence: 99%
“…Durante la hospitalización se detectó la presencia de megalencefalia, que en la AG-1 puede estar presente desde el nacimiento o desarrollarse en las primeras semanas o meses de vida, con lo que se convierte en el signo de aparición más precoz (1,4,9,10).…”
Section: Discussionunclassified